2003
DOI: 10.1034/j.1600-051x.2003.20016.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at position −174 of IL‐6 gene is associated with susceptibility to chronic periodontitis in a Caucasian Brazilian population

Abstract: We concluded that the IL-6-174 polymorphism is associated with susceptibility to chronic periodontitis in the population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 39 publications
7
117
3
6
Order By: Relevance
“…However, in this study, IL-6 GG genotypes could not modify the risk of chronic periodontitis but increased the risk of aggressive periodontitis. Several studies have been published on whether the IL-6 polymorphism predisposes to periodontitis (29)(30)(31). However, the results of studies on the associations between these polymorphism and clinical forms of periodontitis are contradictory (13,19,32,33).…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 93%
“…However, in this study, IL-6 GG genotypes could not modify the risk of chronic periodontitis but increased the risk of aggressive periodontitis. Several studies have been published on whether the IL-6 polymorphism predisposes to periodontitis (29)(30)(31). However, the results of studies on the associations between these polymorphism and clinical forms of periodontitis are contradictory (13,19,32,33).…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 93%
“…First, Trevilatto et al reported an association between IL-6(-174) gene polymorphism and CP in the Caucasian race. 11 After that,several studies found different results regarding the relationship between IL-6(-174) gene polymorphism and periodontal disease. Some of these studies did not find any association between IL-6(-174) gene polymorphism and CP, 12,13,14,15 however some others found associations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the host response is influenced by several possible risk factors including genetic factors. Previous studies indicated that chronic periodontitis (CP) may have a genetic background (12,13), as well as PID (14,15).…”
Section: Introductionmentioning
confidence: 99%